1977
DOI: 10.1136/bmj.2.6100.1450
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive measurement of human fetal circulation using ultrasound: a new method.

Abstract: We combined two ultrasound techniques to develop a safe, non-invasive, transcutaneous method of observing the circulation in the umbilical arteries and vein in the fetus. The umbilical cord can be located by standard echo ultrasound procedures, and this information can be used to direct a Doppler ultrasound beam on to the vessels in the cord. The signals can be heard through audio headphones or recorded on a tape recorder and spectrum-analysed. The method was successful in each of 20 patients examined, whose p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
135
0
8

Year Published

1996
1996
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 357 publications
(143 citation statements)
references
References 4 publications
0
135
0
8
Order By: Relevance
“…4 A meta analysis of randomized controlled trials of UA Doppler velocimetry (2013) in high risk pregnancies (mainly pregnancies associated with hypertension and suspected IUGR) demonstrated that its use was associated with a trend toward reduction in perinatal mortality, although there was no effect on neonatal morbidity. 5 Present study is an effort to establishing the role of UA Doppler ultrasound in predicting adverse perinatal outcome in hypertensive disorders of pregnancy and to determine its role in clinical management of such pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…4 A meta analysis of randomized controlled trials of UA Doppler velocimetry (2013) in high risk pregnancies (mainly pregnancies associated with hypertension and suspected IUGR) demonstrated that its use was associated with a trend toward reduction in perinatal mortality, although there was no effect on neonatal morbidity. 5 Present study is an effort to establishing the role of UA Doppler ultrasound in predicting adverse perinatal outcome in hypertensive disorders of pregnancy and to determine its role in clinical management of such pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Several published studies have confirmed the importance of assessment of the cerebral circulation as an indicator of fetal hypoxia. [11,[15][16][17][18] A total of 100 cases, 50 cases from normal pregnant women, i.e., (control group) and 50 cases from the high-risk group, i.e., (study group) were studied in II and IIItrimesters of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…[12,15,16,18,20] The brain sparing effect denotes the redistribution of available blood from the abdominal and peripheral vessels to the brain which is a vital organ requiring adequate perfusion. [11,13,16] …”
Section: S/d Ratiomentioning
confidence: 99%
See 2 more Smart Citations